Sustainability balanced scorecard: Four performance perspectives or more? - Rašić-Jelavić Sanda; Pajdaković-Vulić Mirna (Strategic Management, 2021)
This paper analyzes the Sustainability Balanced Scorecard (SBSC) as a renewed framework for measuring and managing sustainability performance of a company. The paper presents the main characteristics of original Balanced Scorecard (BSC), explains its purpose and main performance perspectives. Based on literature review, paper address the various approaches to design and prioritize performance perspectives within the SBSC. Firstly, casual links within and between performance perspectives are described: hierarchical links (as is in original BSC approach), semi-hierarchical links and network links. Secondly, the paper explains how the sustainability issues are incorporated within SBSC framework. Several solutions are explained as suggested in the literature: (1) adding additional single or multiple performance perspectives to deal with strategically important sustainability issues, (2) incorporating sustainability aspects within original four performance perspectives, (3) adding additional sustainability perspectives and incorporating sustainability aspects in four original performance perspectives simultaneously, (4) organize separate SBSC for managing only sustainability issues. Specific features of these approaches are explained as well as appropriateness of their application in practice. Advantages and disadvantages of SBSC are highlighted and recommendations for future research.